PENERAPAN SANKSI BAGI SANTRI BERMASALAH DI PONDOK PESANTREN NURUL JADID PERSPEKTIF TEORI PENEGAKAN HUKUM LAWRENCE M. FRIEDMAN - miftah, mushafi; Hidayatullah, Syarif; Aisyah, Siti (At-Turost : Journal of Islamic Studies, 2021)
This study discusses the problems of applying bald sanctions for students who have problems in PP. Nurul Jadid. The purpose of this study was to determine the root cause of the application of bald sanctions against problematic students. Due to the fact, the sanction is not a deterrent reason for santri not to violate the rules of the pesantren. As an analytical tool for the problematic application of the bald sanction is the law enforcement theory of Lawrence M. Friedman. Therefore, the formulation of the problems that arise from this research are; 1) what are the sanctions given to students who have problems in PP. Nurul Jadid? 2) What is the basis for applying sanctions for students who have problems in PP. Nurul Jadid? 3) how are the problems of applying sanctions for students who have problems in PP. Nurul Jadid Paiton Probolinggo? While the purpose of this study is to find out the sanctions given to students who have problems in PP. Nurul Jadid, to find out the basis for applying sanctions for students who have problems in PP. Nurul Jadid den to find out the problems of applying sanctions for students who have problems in PP. Nurul Jadid Paiton Probolinggo. Keywords: Sanctions, Problematic Students, and Law Enforcement Theory